Determinants and reasons for dropout in swimming - Systematic review - Monteiro, D.; Cid, L.; Almeida Marinho, D.; Moutao, J.; Vitorino, A.; Bento, T. (Sports, 2017)
The present research aims to systematically review the determinants and reasons for swimming dropout. The systematic review was conducted through electronic searches on the Web of Knowledge and PsycInfo databases from 2 February to 29 July 2015, using the keywords dropout, withdrawal, motives, reasons, sport, framework-theories, motivation, swim*, review, attrition and compliance. Fifteen studies were found and six were fully reviewed and its data extracted and analysed. Most studies were undertaken in Canada and in the United States of America (USA), and one study was conducted in Spain. Most participants were female (65.74%), and the main reasons for dropout were `conflicts with their trainers`, `other things to do`, `competence improvements` failure`, `parents, couples or trainers` pressure`, `lack of enjoyment` and `get bored`. This review contributes to the present knowledge on the understanding of dropout in swimming. However, it is necessary to continue researching on this topic, validating measurement instruments and studying the motivational processes related to dropout and persistence